Study of Two Different Field Measurement Methods of Infiltration: Falling Head and Constant Head, at Various Hydraulic Head - Enny Dwi Wahjunie; Wahyu Purwakusuma; Sri Malahayati Yusuf (Jurnal Ilmu Tanah dan Lingkungan, 2024)
Two field measurement of infiltration rate methods had been performed on Latosol (Oxic dystrudept) Dramaga Bogor in order to investigate the opportunity to generate different result due to the different of hydraulic head applied and the different way of water was supplied. They were constant head and falling head methods. Falling head method was done in two different ways, namely within a certain time interval and within a certain water level interval. Hydraulic head used during measurement were of 10 cm, 15 cm, and 20 cm. The falling head and constant head method, clearly, generated different minimum infiltration rate values The falling head method measured on a fixed time interval generated almost the same values of minimum infiltration rate, respectively of 4.8 cm hour -1, 5.5 cm hour -1, and 4.8 cm hour -1 at 10 cm, 15 cm, and 20 cm hydraulic head. The falling head method based on bulk water level interval at 10 cm, 15 cm, and 20 cm generated minimum infiltration rate values respectively of 13.2 cm/hour, 12.8 cm/hour, and 18.8 cm/hour. The constant head method at 10 cm, 15 cm, and 20 cm hydraulic head generated minimum infiltration rate values respectively of 11.0 cm/hour, 18.5 cm/hour, and 19.0 cm/hour. The values were higher than of the fixed time interval based falling head method. Infiltration field measurement using the falling head method either based on time interval or water level interval did not show an increasing trend of minimum infiltration rate values due to the increase of hydraulic head. However, the infiltration field measurement using constant head showed an increasing trend of the minimum infiltration rate values due to the increase of hydraulic head.